(DE)CANONIZATION OF PUSHKIN AND PAVIC - BETWEEN THE STATUS OF NATIONAL AND WORLD LITERARY CLASSICS (Heritage, 2024)
The paper examines the process of national and world canonization of Alexander Sergeyevich Pushkin and Milorad Pavić, as well as the efforts to decanonize these writers and revalue their works from the point of view of reductive political reception and to treat them as paraliterary givers of legitimacy to hegemonic national politics. Such tendentious and simplified evaluations of the representative writers’ of two Slavic literatures largely arise from the image of ​​the Yugoslav and (post)Soviet crises starting at the end of the 1980s, as well as from geopolitical efforts to rearrange the mentioned areas politically, culturally and nationally. Such reductive interpretations as imposed by the prevailing part of the Western political and media discourse – the key feature of which is the thesis about Serbian and Russian responsibility for war conflicts and the disintegration of socialist Yugoslavia and the Soviet Union – conditioned not only a malicious attitude towards the constitutive factors of Serbian and Russian political existence, but also the manifestation of a discriminatory attitude towards the culture of sanctioned ‘political opponents’.
Keywords: literary canon, Russian literature, Serbian literature, political reception, Aleksandar Pushkin, Milorad Pavić